(untitled) (Archives of Clinical and Medical Case Reports, 2021)
FAM20A is a Protein Coding gene. It acts as an allosteric activator of the Golgi serine/threonine protein kinase FAM20C and is involved in biomineralization of teeth. A novel homozygous deletion mutation in exon 11 of FAM20A has been described in five members from a large consanguineous Bedouin family, all five with hypoplastic-hypocalcified AI and unerupted and crown resorbed permanent molars, a very rare phenotype. Deciduous mandibular canines and first molar, and maxillary first and second molars of an affected girl were compared to normal pair-matched teeth. Slices of the teeth were examined using SEM, and the ion content of enamel and dentine was determined using Energy Dispersive X-ray Spectrometer (EDS). The deciduous teeth showed missing enamel and the dentin was hypercalcified with very few open tubuli. Calcium and phosphorous percentages were reduced by 45 % in the enamel, and extensive apposition of secondary dentin and calcification of the pulps was observed. The permanent dentition showed impacted molars, premolars and canines with hypoplastic enamel and reduced dimensions of the erupted teeth. The mutation of FAM20A caused a peculiar type of AI with very thin amorphic enamel, infraoccluded deciduous teeth and impacted permanent canines, premolars and molars.